Nanocalipers as novel molecular scaffolds for carbon nanotubes. Issue 5 (10th April 2017) - Liu, Gang; Miyake, Yuya; Komatsu, Naoki
Abstract : Nanocalipers were synthesized by connecting directly the five aromatic moieties including two receptors, two corners and a core, and found to discriminate the diameter, metallicity and handedness of carbon nanotubes through selective complexation. Abstract : We have been developing host–guest chemistry for separation of carbon nanotubes (CNTs) according to diameter, metallicity, and even handedness. The host molecules named "nanotweezers" consisting of a rigid core and two receptors were designed and applied to CNT separation. To apply this methodology for separation of a wider range of CNTs with better selectivity, "nanocalipers" have been designed, which include a core, two corners, and two receptors. In this review, we focus on "nanocalipers", new host molecules next to the nanotweezers, from their molecular design and synthesis to CNT separation.